Barriers and Facilitators to Successful Hypertension Management in Older Adults from the Perspectives of Community Health Nurses: : A Qualitative Study - Thongtaeng, Pulawit; Seesawang, Junjira (Nursing Science Journal of Thailand, 2021)
Purpose: To explore community health nurses (CHNs)’ perspectives on specific barriers and facilitators to successful hypertension management for older adults in rural communities. Design: Descriptive qualitative study. Method: Semi-structured interviews were conducted with 25 community health nurses who were responsible for hypertension management for older adults at health promoting hospitals in rural areas. Data were collected with a tape-recorder and transcribed verbatim. Data were analyzed using content analysis. Main findings: The community health nurses identified barriers to successful hypertension management for older adults: 1) barriers from community health nurses (including work overload and lack of knowledge for hypertensive counseling) and 2) barriers from patients and family (including noncompliance to lifestyle modification, negative self-beliefs of patients, and avoid becoming a burden to family). Major facilitators were: 1) collaborative partnership (including creating partnerships with family and healthcare volunteers) and 2) information (including providing information about current health status). Conclusion and recommendations: This study promotes understanding of community health nurses’ perspective of facilitators and barriers to hypertension management for older adults in rural areas. However, successful implementation will be contingent upon addressing barriers such as balancing the community health nurses’ workload and promoting patients’ compliance to lifestyle changes. Further research is recommended to explore self-care management to control their blood pressure among older adults.